2022
DOI: 10.2174/1386207325666220128114547
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Against COVID-19 Inflammation: A Mini-Review

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is a virus whose genetic material is positive single-stranded RNA, being responsible for coronavirus disease 2019 (COVID-19), an infection that compromises the lungs and consequently the respiratory capacity of the infected individual, according to the WHO in November 2021, 249,743,428 cases were confirmed, of which 5,047,652 individuals died due to complications resulting from the infection caused by SARS-COV-2. As the infection progresses, the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…However, patients with diabetes and another disease could interfere with Tocilizumab therapy, affecting the optimal management of SARS‐CoV‐2 infection. Natural products with easy distribution and low toxicity have gained a lot of attention based on their great antiviral activities against different viruses, especially against the life‐threatening coronavirus 104,105 . therefore, the discovery of new active compounds to develop anti‐inflammatory drugs is an essential step for Covid 19 treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients with diabetes and another disease could interfere with Tocilizumab therapy, affecting the optimal management of SARS‐CoV‐2 infection. Natural products with easy distribution and low toxicity have gained a lot of attention based on their great antiviral activities against different viruses, especially against the life‐threatening coronavirus 104,105 . therefore, the discovery of new active compounds to develop anti‐inflammatory drugs is an essential step for Covid 19 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products with easy distribution and low toxicity have gained a lot of attention based on their great antiviral activities against different viruses, especially against the life-threatening coronavirus. 104,105 therefore, the discovery of new active compounds to develop anti-inflammatory drugs is an essential step for Covid 19 treatment. Flavonoids like naringenin have been discovered to play potential pharmacological effects.…”
Section: Cell or Tissue Type/animals Dosage Anti-inflammatory Activit...mentioning
confidence: 99%
“…In addition, natural products also contain a variety of active compounds possessing anti-inflammatory activities in repressing the crucial driven cytokine and signaling pathway such as IL-6 and NF (nuclear factor)-κB, respectively 13 . Their therapeutic potential against COVID-19 inflammation also has been noticed and studied 14 . Musa paradisiaca L., prevalently known as banana, is an herbaceous plant of the Musaceae family and the genus Musa .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, some commonly used edible plant in families (such as senna, licorice, ginger, rosemary, and Lonicerae japonicae flos), have now been widely used for attenuating the main clinical symptoms of COVID-19 in most of Chinese families [8,[12][13][14][15] . Increasing studies have demonstrated that parts of natural constituents in plant extracts exhibit various health-promoting effects including anti-oxidative, anti-inflammatory, anti-thrombotic and anti-viral effects, which inspired us to further decipher the anti-SARS-CoV-2 substances in plant extracts, as well as to uncover their anti-SARS-CoV-2 mechanisms [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%